The Role of Family Policy in Solving Demographic Problems: Study of the Polish Program Family 500+ - Wilk, Sławomir (European Journal of Sustainable Development, 2020)
This article offers a critical reflection on the Programme “Family 500+” introduced by the Polish government and aimed at improving the financial situation of Polish families in order to increase the fertility rate. Families have been supported with the benefit of 500 PLN given for each child under 18. The article presents the results of the research carried out in 2019 on the representatives of the households (N= 3347). The interviewees most frequently pointed to the increase of the quality of living conditions and the increase in the consumption of goods and services. Approximately 80% of the interviewees have noticed the fact that the benefit boosted potential development of children by enabling them to participate in the extracurricular activities and visit leisure centers. 64,7% of the interviewees believe that the Programme let them have savings and 17,8% of respondents claim that the benefit will not contribute to their savings but will be consumed on a day-to-day basis. Despite the initial assumptions of the Programme , the policy of pronatalism was not achieved as the fertility rate did not reach the assumed level. It must be stated that even though the legislative activities constitute a milestone in the Polish pro-family policy these solutions have many disadvantages. The Programme should not be the main tool of the Polish demographic policy but just supplementary. Keywords: Family 500+ Programme; family policy; demographic policy; State Aid for Child Support Act; household finance; family benefits